ТЕХНОГЕН ЦИВИЛИЗАЦИЯ ГЛОБАЛЛАШУВ ЖАРАЁНИНИНГ ИЖОБИЙ ВА САЛБИЙ НАТИЖАЛАРИ - Очилов, Ж.А. (SCIENCE and SOCIETY, 2017)
Tne article deals with objective conditions and subjective factors of globalization of the results and technogen civilization and its positive and negative results in the context «mental regurements». The author analyses theoretical-methodological meanings and practical directions and changes of this process.
Keywords: technogenic civilization; determinating factors; anomal globalization; globalization of technogenic civilization; humanization; new humanism; paradygms of technogenic civilization; humanistic values; technological determinism; globalization of civilizations; effective civilization